Pengembangan E-Modul Berbasis Masalah dengan Pendekatan Etno-STEM pada Materi Gelombang Bunyi untuk Meningkatkan Minat dan Hasil Belajar Peserta Didik - Neni Nur Afia; Sugianto; Ellianawati; Isa Akhlis (Universitas Negeri Semarang, 2025)
Learners' perception that physics is difficult and low interest in learning cause learning outcomes to decline. The Problem-Based Learning (PBL) model encourages students' activeness through exploration and discussion, while the ethno-STEM approach makes learning contextual with Javanese culture by improving 21st century skills. This study aims to develop a problem-based e-module with an ethno-STEM approach on sound waves material to increase interest and learning outcomes. Using the Research and Development (R&D) research type with the ADDIE method and One Group Pre-Test Post-Test design, small-scale trials were conducted in class XII-9 and large-scale in class XI-4 SMA Negeri 1 Ngawen. The results showed: (1) E-modules obtained an average score from validators of 89.42% with a very feasible category; (2) Learning interest increased by 4.25% with N-gain 0.13 and effect size 1.651, while learning outcomes increased by 27.21% with N-gain 0.46 and effect size 1.800. There was a moderately positive correlation between the increase in interest and learning outcomes (0.456); (3) Practicality reached 76.04% (class XII-9) and 73.92% (class XI-4) with the practical category. Problem-based e-modules with ethno-STEM approach proved to be feasible, effective, and practical for learning sound waves.